2021
DOI: 10.1002/ijgo.13825
|View full text |Cite
|
Sign up to set email alerts
|

Oncophone20 study: Patients’ perception of telemedicine in the COVID‐19 pandemic during follow‐up visits for gynecological and breast cancers

Abstract: The COVID-19 pandemic has increased the burden on healthcare systems worldwide. In order to ensure adequate clinical and psychological care, maintaining home confinement, patients were included in a multidisciplinary tele-assistance network. Based on the results obtained during the pandemic, many experts of "integrated care" and "patient-centered care" encouraged telemedicine as an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Additionally, eight studies assessed caregivers' satisfaction and experiences with telehealth. Three studies evaluated satisfaction with the use of telemedicine among new patients Identified studies covered mainly the patient's satisfaction with telemedicine during COVID-19 pandemic across an extensive range of medical specialties: Neurosurgery [8][9][10][11], Primary Care [12,13], Dermatology [14], Obstetrics [15], Orthopedics [16][17][18], Oncology [19][20][21][22][23][24][25], Rheumatology [26][27][28][29], Otolaryngology [30][31][32][33][34][35], Urogynecology [36], Cardiology [37], Psychiatry [38], Internal Medicine [39], Allergology [40,41], Endocrinology [42], Gastroenterology [43], Spinal Disorders [44][45][46], Oral and Maxillofacial Surgery [47], Surgery [48][49][50][51], Ophthalmology [52,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, eight studies assessed caregivers' satisfaction and experiences with telehealth. Three studies evaluated satisfaction with the use of telemedicine among new patients Identified studies covered mainly the patient's satisfaction with telemedicine during COVID-19 pandemic across an extensive range of medical specialties: Neurosurgery [8][9][10][11], Primary Care [12,13], Dermatology [14], Obstetrics [15], Orthopedics [16][17][18], Oncology [19][20][21][22][23][24][25], Rheumatology [26][27][28][29], Otolaryngology [30][31][32][33][34][35], Urogynecology [36], Cardiology [37], Psychiatry [38], Internal Medicine [39], Allergology [40,41], Endocrinology [42], Gastroenterology [43], Spinal Disorders [44][45][46], Oral and Maxillofacial Surgery [47], Surgery [48][49][50][51], Ophthalmology [52,…”
Section: Methodsmentioning
confidence: 99%
“…It should be mentioned that the rate of missed virtual visits is significantly lower compared with in-person encounters, which has financial implications [12]. The time and cost savings of having a consultation with a medical professional from one's workplace or home is one of the other advantages of telemedicine emphasized by respondents [20].…”
Section: Advantages Of Telemedicinementioning
confidence: 99%
“…The final version of the C-SUTAQ contained 22 items, the original six subscales were confirmed which is the same as the original 19 and Italian version. 20 However, in the Norwegian version, the original subscales were not confirmed, although it revealed good internal consistency, with a Cronbach alpha of 0.851. 18 The Norwegian results indicated that a one-factor solution, or at most a three-factor solution, was sufficient, as the explained variance increased by < 6% when adding more factors.…”
Section: Discussionmentioning
confidence: 91%
“… 16 The instrument showed satisfactory results for reliability and validity and had been translated and applied in telemedicine services in countries such as Italy and Norway. 16 , 18 , 20 The SUTAQ was considered an appropriate method for testing the acceptance of telecare technology.…”
Section: Introductionmentioning
confidence: 99%
“…Even when cancellations recovered after lockdown phases, the use of electronic portals continued to increase, indicating the prolonged uptake of telemedicine among BC patients [ 56 ]. Telemedicine was widely accepted by BC patients [ 91 , 92 , 94 ] and clinicians [ 55 ] during the pandemic, and this satisfaction was slightly lower for surgical oncology visits [ 90 ]. Women identified telemedicine as a positive alternative to rehabilitation appointments when centres were closed during COVID-19 [ 7 ].…”
Section: Resultsmentioning
confidence: 99%